Acesso e permanência de alunos de engenharia da UTFPR - Câmpus Medianeira - Gómez, Magela Reny Fonticiella [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work consists in a research of bibliographic and documental nature, that aimed to to evaluate the admission, the permanency and the consequent evasion, focusing specifically on the Engineering superior courses of UTFPR Câmpus Medianeira. The university's history was rescued and also the involved courses, since its beginning and the Brazilian reality was discussed as a way to contextualize the problem. Statistical data about the school evasion in the Brazilian Higher Education were collected, seeking to relate them with the indicators of the Universidade Tecnológica Federal do Paraná and the Câmpus Medianeira. The raised and analyzed factors were investigated by the academic system information about the statistical data of permanency and evasion features. A very expressive factor was to find how the geographic mobility happens in the country and in the region where the IES investigated is located, considering that it is adopted the process of candidate selection (access) to the courses with the ENEM average by the SiSU process. A very expressive factor was to verify how the geographical mobility of these students in the country and in the region where the IES investigated is located, once the process of candidate selection (access) is adopted to the courses with the ENEM's grade by the SiSU process. An increasing bias for the access to the Higher Education occurs due to the increasing of the vacancy in IFES and to the high students' mobility enabled by the SISU. The data analysis was performed from the information categorization, showing the evasion reasons. It was verified that the evasion rates have fallen since the course consolidation and, mainly, because of the public policies implanted. Therefore, strategies and affirmative actions need to be effectively incremented and enlarged to guarantee the permanency of these students in the university, creating mechanisms that ensure their course's conclusion.

O presente estudo constitui-se de pesquisa de natureza bibliográfica e documental que teve como objetivo avaliar o ingresso, a permanência e a decorrente evasão, com enfoque específico sobre os cursos superiores de Engenharia na UTFPR - Câmpus Medianeira. Resgatou-se a história da universidade, dos cursos envolvidos desde seu surgimento, e discutiu-se a realidade brasileira como forma de contextualização do problema. Dados estatísticos sobre a evasão escolar no ensino superior brasileiro foram coletados, buscando-se relacioná-los com os indicadores da Universidade Tecnológica Federal do Paraná e o Câmpus Medianeira. Os fatores levantados e analisados foram investigados por meio de informações do sistema acadêmico acerca da permanência e caracterização da evasão. Um fator muito expressivo foi constatar como acontece a mobilidade geográfica desses estudantes pelo país e pela região onde se encontra localizada a IES investigada, uma vez que é adotado o processo de seleção de candidatos (acesso) aos Cursos com a nota do ENEM pelo processo do SiSU. Um viés da ampliação do acesso ao Ensino Superior ocorre em virtude da ampliação das vagas nas IFES e pela alta mobilidade geográfica permitida pelo SiSU. A análise dos dados foi realizada a partir da categorização das informações, evidenciando-se os motivos da evasão. Constatou-se, porém, que as taxas de evasão caíram a partir da consolidação dos cursos e pelas políticas públicas educacionais implementadas. Contudo, estratégias e ações afirmativas precisam ser efetivamente incrementadas e ampliadas para garantir a permanência na universidade desses estudantes, criando-se mecanismos que garantam a conclusão de seus cursos.
Keywords: Ensino superior; Politicas publicas; Universidades e faculdades - Ingresso; Evasão escolar; Engenharia - Estudo e ensino - Paraná; Public policy